REPRESENTASI KULTURAL LAKI-LAKI DAN PEREMPUAN DALAM KISAH “PUTRI LUNGO” - Heksa Biopsi Puji Hastuti (TELAGA BAHASA, 2016)
The issue raised in this paper is how the cultural representation of men and women in "Putri Lungo" folktale? Data in the form of prose, "Putri Lungo" folktale, narrated orally. The analysis was conducted with qualitative methods using an anthropological approach. The results of analysis show that the representation of men in the story "Princess Lungo" inherent in Lampae figures. One man above all is to have the ability to decide something. A man had to prepare his best before accepting responsibility. When it assumed responsibility as the head of the family, a man should be able to meet its obligations to earn a living in order to meet the needs of the family. Meanwhile, women in "Putri Lungo" folktale is represented by two characters, the mother and Princess Lungo. It is read that women have right to make a request as a condition of receipt of the marriage proposal. In addition, women are culturally carrying out the functions of educators in the household. When living together in the bond of household, strategic decisions are in the hands of the husband as head of the family and the wife is obliged to support the decision.